Penggunaan Media Boneka Tangan untuk Peningkatan Hasil Belajar Siswa Dalam Menjawab Isi Dongeng - Deden Hendriyawan; Yesie Kusumaningrum; Uli Damaianti (Institute of Advanced Knowledge and Science, 2024)
Looking at the learning outcomes of Class III students at SDN Cogreg 02 Tangerang Regency in the Indonesian language subject, especially the material answering the content of fairy tales, it is considered that they do not meet the Minimum Completeness Criteria (KKM), through this research it is hoped that it will be able to increase student participation and learning outcomes. Improvement efforts were made by using hand puppets to attract students' interest. The research method used is descriptive quantitative. This type of research uses the Hopkins research model in the form of a spiral with action research stages in a cycle that includes planning, action, observation and reflection. Research data collection uses observation, interviews, tests and documentation methods. The research was carried out using hand puppets for 2 cycles. The increase in learning outcomes in answering the content of students' fairy tales from cycle 1 to cycle 2 increased by 35%. From the results of this research, it can be concluded that learning media in the form of hand puppets is able to improve learning outcomes in answering the content of fairy tales for Class III students at SDN Cogreg 02, Tangerang Regency.